The role of auditing in strengthening sovereign wealth funds and its impact on sustainability (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to highlight the theoretical framework of the concept of sovereign wealth funds, their importance and types. And measuring the impact of sustainability in its three dimensions (environmental, economic and social) on the organization’s performance. Explaining the role of auditing in enhancing the quality of financial and non-financial data and enhancing the sustainability of the resources of sovereign wealth funds as they are an economic tributary to the country. That is why most developed countries have focused on making sovereign wealth funds among their priorities to achieve economic, social and environmental goals, in a direction that does not have a negative impact on sustainability variables. This stems from the importance of sovereign wealth funds and their ability to influence economic and political stability, especially in times of crisis. , by ensuring the stability and continuity of permanent government spending programs and policies to achieve sustainability. The analysis and measurement of research variables and the practical results of the applied aspect were relied upon through a set of statistical measures and reliance on the financial data of the Iraq Fund for External Development, the research sample, and generalizing the extracted results to build conclusions. And provide some possible recommendations from researchers. The researchers believe that in applying the balanced scorecard, the Development Fund must take into account all its axes and not focus on the financial axis only because it does not give a clear picture of the unit’s performance. In addition to the necessity of developing strategic plans to operate the Fund’s resources well in order to achieve a satisfactory level of profits, the management should The Fund applies the balanced scorecard as an integrated framework because it achieves many advantages such as competition, in addition to the necessity of using financial and non-financial indicators in the measurement process when using the sustainable balanced scorecard. The research concluded the importance of the Development Fund management paying attention to non-financial measures to measure the unit’s performance, such as customer satisfaction. Improving services, and paying attention to the environment and society.